2012
DOI: 10.1111/jicd.12000
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the role of stress in periodontal etiopathogenesis: an evidence‐based review

Abstract: Periodontal disease is a multifactorial disease affecting the supporting tissues of the teeth, resulting in progressive attachment loss and bone loss. Periodontal disease is influenced by various systemic, environmental, and psychologic factors that have the potential to alter periodontal tissues and host immune response, resulting in more severe periodontal destruction. Several studies have documented the relationship between psychosocial stress and chronic forms of periodontal disease. Stress impairs periodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…Overall there is evidence that noise, as a source of stress present in everyday life over which individuals cannot exert control, produces transient suppression of immune function, increased oxidative stress, and endocrinal dysfunction, making it plausible to hypothesize its association with increased inflammatory responses and/or a predisposition to new or aggravated existing infections. These are also compatible with previous studies regarding stress and periodontitis . Additionally, stress could affect periodontitis indirectly.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Overall there is evidence that noise, as a source of stress present in everyday life over which individuals cannot exert control, produces transient suppression of immune function, increased oxidative stress, and endocrinal dysfunction, making it plausible to hypothesize its association with increased inflammatory responses and/or a predisposition to new or aggravated existing infections. These are also compatible with previous studies regarding stress and periodontitis . Additionally, stress could affect periodontitis indirectly.…”
Section: Discussionsupporting
confidence: 92%
“…These are also compatible with previous studies regarding stress and periodontitis. [34][35][36] Additionally, stress could affect periodontitis indirectly. Stress could influence oral hygiene 19 and smoking 37 behaviors, which could contribute to periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors might affect plaque scores, PD, and BOP, including stress, medications, smoking, and dental restorations. [30][31][32] The influence of these factors should be addressed in future studies of longer duration and larger sample size. Also, the question whether short-term changes in PD and BOP correlate with long-term success/survival rates of dental implants still remains unanswered.…”
Section: Discussionmentioning
confidence: 99%
“…Psychosocial stress is thought to play an important role in the etiology and progression of periodontal diseases, and the outcome of treatment [4,5]. The relationship between periodontitis and several dimensions of psychosocial distress such as stress, depression, anxiety, life events and poor coping reactions has attracted considerable attention from several groups of researchers during the last three decades [6][7][8][9]. A review showed a strong relationship between periodontal diseases and psychological factors such as stress, distress, anxiety, depression and loneliness [9].…”
Section: Introductionmentioning
confidence: 99%